Evaluation of the neutronic performance of ¹¹B₄C as an alternative coating layer in TRISO fuel - Kourasis, Ioannis; Petropoulos, Nikolaos (HNPS Advances in Nuclear Physics, 2025)
This work explores the viability of using boron carbide (B4C), substantially enriched in ¹¹B at about 99%, conveniently named ¹¹B₄C, as a coating material for Tri-structural Isotropic (TRISO) particle fuel. Utilizing the open source OpenMC VHTR fuel benchmark file as a reference, the SiC coating layer is replaced with ¹¹B₄C at varying enrichment levels to generate three TRISO fuel compact models. Using the models. multiple eigenvalue simulations are conducted with an appropriate number batches of enough thousands of neutrons, calculating the effective multiplication factor, with tallies for the neutron flux spectrum, and neutron absorption by the ¹¹B₄C layer against the reference TRISO with SiC coating. Results show that for highly enriched ¹¹B₄C the fuel element remains critical. For lower ¹¹B enrichment, the expected neutron absorbing properties of ¹⁰B render the fuel element subcritical. Flux spectra and neutron absorption rates are tallied and plotted to further understand the neutronic performance of this coating.